2021
DOI: 10.1093/ajh/hpab046
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence: Expanding the Conceptual Framework

Abstract: Interventions targeting traditional barriers to antihypertensive medication adherence (AHMA) have been developed and evaluated, with evidence of modest improvements in adherence. Translation of these interventions into population-level improvements in adherence and clinical outcomes among older adults remains suboptimal. From the Cohort Study of Medication Adherence among Older adults (CoSMO), we evaluated traditional barriers to AHMA among older adults with established hypertension (N=1544; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 95 publications
0
9
0
1
Order By: Relevance
“…Furthermore, compared to urban-dwelling older people, counterparts from rural areas were inclined to have inadequate medication adherence despite being not significant, which was similar to a study that found that medication adherence was independent of the place of residence [ 32 ]. An increasing body of evidence suggests that older people with depression have poor medication adherence [ 10 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared to urban-dwelling older people, counterparts from rural areas were inclined to have inadequate medication adherence despite being not significant, which was similar to a study that found that medication adherence was independent of the place of residence [ 32 ]. An increasing body of evidence suggests that older people with depression have poor medication adherence [ 10 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…85 Social determinants of health have emerged as a critical component of potentially modifiable disease risk that are inequitably distributed across our populations. Hypertension, a critical risk factor for stroke, is a condition particularly impacted by social determinants of health, 86 and better understanding of the genetic and environmental factors contributing to BP could improve risk modeling as well as stratification of vulnerable populations for targeted intervention to reduce the risk of stroke and related vascular and cognitive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Potential indirect impacts include increase in body mass index due to changes in diet and physical activity, exposure to domestic violence and an increase in mental health disorders such as depression and anxiety (7). These would have special impacts in persons living with chronic diseases such as hypertension (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%